1993
DOI: 10.1177/41.7.8515049
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cysteine and aspartic proteinases, acid phosphatase, and an endogenous cysteine proteinase inhibitor, cystatin-beta, in rat osteoclasts.

Abstract: To understand the bone resorption and lysosomal proteinases in osteodasts, we examined by immunohistochemistry the localization of lysosomal cysteine and aspartic proteinases, acid phosphatase, and cystatin-0 in the rat tibial bone. Immunoreactivity for cathepsins B, C, H, and L, cathepsin D, acid phosphatase, and cystatin-p was demonstrated in various ells of the bone tissue; in patti&, large multinucleated osteoclasts attached to the bone surface and chondrodasts in the proximal growth plate. These cells sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…These protons are thought to be involved in not only the degradation of bone mineral, chiefly solid calcium hydroxyapatite, but also in activation of cysteine proteinases by acidification of the lacunae. The lysosomal proteinases secreted into the lacunae, possibly cysteine proteinases, have been thought to play an important role in osseous collagenolysis [1,[3][4][5][6][7][8] We previously reported [9] that the bone pit formation stimulated by PTH was significantly suppressed by specific inhibitors of cathepsin L and L-type proteinases, but not by those of cathepsins B and D. Moreover, we also demonstrated [10] that the increase in pit formation stimulated by PTH paralleled the increase of a 39 kDa precursor form of cathepsin L secreted into media, and that both increases induced by PTH were markedly inhibited by addition of calcitonin. These findings indicate that the secretion of procathepsin L from osteoclasts is an important process in PTH-induced bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…These protons are thought to be involved in not only the degradation of bone mineral, chiefly solid calcium hydroxyapatite, but also in activation of cysteine proteinases by acidification of the lacunae. The lysosomal proteinases secreted into the lacunae, possibly cysteine proteinases, have been thought to play an important role in osseous collagenolysis [1,[3][4][5][6][7][8] We previously reported [9] that the bone pit formation stimulated by PTH was significantly suppressed by specific inhibitors of cathepsin L and L-type proteinases, but not by those of cathepsins B and D. Moreover, we also demonstrated [10] that the increase in pit formation stimulated by PTH paralleled the increase of a 39 kDa precursor form of cathepsin L secreted into media, and that both increases induced by PTH were markedly inhibited by addition of calcitonin. These findings indicate that the secretion of procathepsin L from osteoclasts is an important process in PTH-induced bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Sannes and colleagues [15] employed MNA substrates for demonstration of dipeptidyl peptidases I and II (DPP-I, DPP-II), and showed DPP-I in osteoblasts, osteocytes, and chondrocytes in proliferating and hypertrophic regions of the growth plate, and DPP-II in osteoblasts, osteocytes, and chondrocytes in the resting zone. In the same experiment, they failed to demonstrate cathepsin B activity in the bone, although it was strongly positive in osteoclasts with other enzyme histochemical [5,20] and immunohistochemical studies [6,9,13,16]. Further, there has been no trial to demonstrate AP-A and DPP-IV activities in the bone.…”
Section: Introductionmentioning
confidence: 97%
“…However, there have been very few papers addressing histochemical localizations of proteases, with the exception of cathepsins B, L and D [5,6,9,13,15,20]. Lipp [10] first reported that aminopeptidase-M (AP-M) activity was present in osteoclasts, osteoblasts and endothelial cells at the vascular invasion in growth plate using Leu-2-naphthylamide as a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Kominami et al immunohistochernitally demonstrated the presence of cathepsin B and L in rat osteoclasts of the bone surface, suggesting the participation of these proteinases in the degradation of the organic constituents of the bone matrix [9]. We previously reported that rat osteoclastic bone resorption induced by parathyroid hormone (PTH) was markedly in- hibited by pig leucocyte cysteine proteinase inhibitor (PLCPI) [IO,1 I], a specific inhibitor of cathepsin L, and by chymos~tin, a selective inhibitor of cathepsin L, but not by CA-074 1121, a specific inhibitor of cathepsin B [13].…”
Section: Introductionmentioning
confidence: 99%